Teaching wholeness in architecture education: advancing Christopher Alexander’s teaching legacy through the Building Beauty program - Ingham, Susan; Ettlinger, Or (Journal of Architecture and Urbanism, 2023)
Architect, builder, and professor Christopher Alexander focused his life’s work on trying to understand what makes the physical environment beautiful, and how beautiful environments can be created today. Through careful research, innovative teaching, and unorthodox professional practice, Alexander formulated a unified vision of the physical environment based on a theory of “wholeness.” He observed that achieving beauty and wholeness in the built environment – as well as teaching it – requires the integration of processes and considerations that are usually kept separate: integrating form and function, integrating teaching and practice, integrating design and construction, integrating projects of various scales, and integrating all of these within the ongoing search for how beauty and wholeness might be reached, taught, and proliferated. Alexander explored and developed ways of implementing these observations throughout his decades of teaching at the University of California at Berkeley, culminating in the Building Process Area of Emphasis, which he founded with his colleagues in 1990. His former students from this period, together with new partners, established “Building Beauty” in 2017, a post-graduate program in architecture that continues to teach and expand upon Alexander’s theories and methods of generating beauty and wholeness in the physical environment.